Geographic and temporal dynamics of a global radiation and diversification in the killer whale. Issue 15 (17th July 2015) - Morin, Phillip A.; Parsons, Kim M.; Archer, Frederick I.; Ávila‐Arcos, María C.; Barrett‐Lennard, Lance G.; Dalla Rosa, Luciano; Duchêne, Sebastián; Durban, John W.; Ellis, Graeme M.; Ferguson, Steven H.; Ford, John K.; Ford, Michael J.; et al.
Abstract Global climate change during the Late Pleistocene periodically encroached and then released habitat during the glacial cycles, causing range expansions and contractions in some species. These dynamics have played a major role in geographic radiations, diversification and speciation. We investigate these dynamics in the most widely distributed of marine mammals, the killer whale (Orcinus orca), using a global data set of over 450 samples. This marine top predator inhabits coastal and pelagic ecosystems ranging from the ice edge to the tropics, often exhibiting ecological, behavioural and morphological variation suggestive of local adaptation accompanied by reproductive isolation. Results suggest a rapid global radiation occurred over the last 350 000 years. Based on habitat models, we estimated there was only a 15% global contraction of core suitable habitat during the last glacial maximum, and the resources appeared to sustain a constant global effective female population size throughout the Late Pleistocene. Reconstruction of the ancestral phylogeography highlighted the high mobility of this species, identifying 22 strongly supported long‐range dispersal events including interoceanic and interhemispheric movement. Despite this propensity for geographic dispersal, the increased sampling of this study uncovered very few potential examples of ancestral dispersal among ecotypes. Concordance of nuclear and mitochondrial data further confirms genetic cohesiveness, with little or no current gene flow among sympatric ecotypes. Taken as a whole, our data suggest that the glacial cycles influenced local populations in different ways, with no clear global pattern, but with secondary contact among lineages following long‐range dispersal as a potential mechanism driving ecological diversification.